2021
DOI: 10.1364/ol.414477
|View full text |Cite
|
Sign up to set email alerts
|

On-chip optical true time delay lines based on subwavelength grating waveguides

Abstract: An optical true time delay line (OTTDL) is a fundamental building block for signal processing applications in microwave photonics and optical communications. Here, we experimentally demonstrate an index-variable OTTDL based on an array of 40 subwavelength grating (SWG) waveguides in silicon-on-insulator. Each SWG waveguide in the array is 34 mm long and arranged in a serpentine manner; the average incremental delay between waveguides is about 4.7 ps, and the total delay between the first and last waveguides is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…To solve this issue, optical true time delay line (OTTDL) has been in-troduced as an effective solution by steering the beam at a same angle for a wide bandwidth to salve the bandwidth limitation of traditional electronic phased array antennas. By controlling the phases and the amplitudes of OTTDL transmissions, it is possible to achieve beam steering and beam forming [14][15][16]31,42,44,45 , and satellite navigation communications and automotive ranging radars for Ku and K band have attracted people's attention. The present chip-scale programmable silicon photonic processor can be configured as 4-channel OTTDL for 18 GHz microwave signal and demonstrate the beamformer covering the Ku and K band.…”
Section: Tunable Delay Line and Microwave Photonic Beamformermentioning
confidence: 99%
See 1 more Smart Citation
“…To solve this issue, optical true time delay line (OTTDL) has been in-troduced as an effective solution by steering the beam at a same angle for a wide bandwidth to salve the bandwidth limitation of traditional electronic phased array antennas. By controlling the phases and the amplitudes of OTTDL transmissions, it is possible to achieve beam steering and beam forming [14][15][16]31,42,44,45 , and satellite navigation communications and automotive ranging radars for Ku and K band have attracted people's attention. The present chip-scale programmable silicon photonic processor can be configured as 4-channel OTTDL for 18 GHz microwave signal and demonstrate the beamformer covering the Ku and K band.…”
Section: Tunable Delay Line and Microwave Photonic Beamformermentioning
confidence: 99%
“…Since each channel of the 4channel OTTDL haves 5-bit delay states, there are 2 5 delay states available flexibly by controlling the MZSs. For the 18 GHz microwave photonic beamformer, the minimum delay time Δτ is given by 16…”
Section: Tunable Delay Line and Microwave Photonic Beamformermentioning
confidence: 99%
“…The basic element of the photonic integrated circuit (PIC), which is essential for fulfilling beamsteering, is the delay line (DL). The DL can be implemented using Mach-Zehnder interferometers (MZI), 4-6 photonic crystals (PC), 7,8 integrated Bragg gratings (IBG), [9][10][11][12] microring resonators (MRR), 3,13,14 and arrayed waveguide gratings (AWG). Thus, the proposed PIC design for beamsteering contains the following elements: Mach-Zehnder modulator (MZM), couplers, splitters, and delay lines based on MZI.…”
Section: The Approaches To Implement Ttd Based On the Photonic Integr...mentioning
confidence: 99%
“…In 2020, they demonstrated a discretely tunable TTD using a serial array of 10 SWG waveguide BGs with a total time delay ∼60 ps in steps of ∼6.6 ps over an operating bandwidth of 41.7 nm [154]. Later in 2021, they extended it to 40 SWG waveguides in SOI and showed that by controlling the duty cycles, an average incremental delay of 4.7 ps and a total delay between the first and last waveguides of approximately 181.9 ps can be obtained [161].…”
Section: Waveguide Bragg Gratingmentioning
confidence: 99%